The Demand for Executive Skills - Stephen Hansen; Tejas Ramdas; Raffaella Sadun; Joseph Fuller (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We use a unique corpus of job descriptions for C-suite positions to document skills requirements in top managerial occupations across a large sample of firms. A novel algorithm maps the text of each executive search into six separate skill clusters reflecting cognitive, interpersonal, and operational dimensions. The data show an increasing relevance of social skills in top managerial occupations, and a greater emphasis on social skills in larger and more information intensive organizations. The results suggest the need for training, search and governance mechanisms able to facilitate the match between firms and top executives along multiple and imperfectly observable skills.
Keywords: 330